(untitled) (The Research of Medical Science Review, 2025)
Background: Tennis elbow (lateral epicondylitis) is a popular condition of overuse injury resulting in the pain of tendons at the elbow and the loss of function. There are different ways of treatment and the common ones include the use of autologous blood injection (ABI) and the use of steroid injections. These two treatments focus on reducing pain and promoting healing but their effectiveness continues to remain a controversial issue. Objectives: To match the effectiveness of autologous blood injection (ABI) and steroid injection in the management of tennis elbow as per its effect on relieving pain, functional but also long-term effects. Study design: A cross sectional study. Places and duration of study: Place and Duration of study: October 2024 to March 2025, Orthopedics Surgery Department, Bolan Medical College / Hospital Quetta. Balochistan. Methods: This cross sectional study Conducted in Orthopedic Surgery Bolan Medical College / Hospital Quetta. Balochistan. entailing 60 patients with tennis elbow was carried out. The participants were sorted into two categories; those who received injections of autologous blood and the other group which had steroids infused in them. Visual analog scales (VAS) and Disabilities of the Arm, Shoulder and Hand (DASH) score were used to determine the level of pain, functional scores and recovery times at baseline point, 6 weeks and 3 months after the treatment. Results: There were 60 patients in the study, whose mean age was 45.2 years (SD 7.8). A statistically significant difference was observed in term of pain reduction and functional recovery at 3 months in the group that received ABI to that of the steroid group (p- value of less than 0.05). The ABI group showed reduced rate of recurrence of symptoms with a more prolonged effect. The group taking steroids got pain relief quicker but the short acting effects could not last as long. Neither of the two treatments was poorly accepted, and there were no significant complications in both groups. Conclusion: Autologous blood injection (ABI) has longer-term analgesia and better functional results than steroid injection with regard to tennis elbow. In comparison, although relief provided by steroids works more quickly, ABI can be linked to fewer relapses and more favorable long-term outcomes. The two can be used to treat it, although ABI promises a longer healing without tendon damage unlike the repeated use of steroids